A Case of Hypothyroidism Cured by Natrum Muriaticum (Advancements in Homeopathic Research, 2022)
A case of hypothyroidism treated by constitutional  homoeopathic medicine is presented here with  serial thyroid function test reports. It is worthwhile  mentioning here that initially she had high T3, T4 and  low TSH for which she was given Neomercazole.  Later her TSH became raised and was given Thyrocab,  Eltroxin etc. She was perturbed due to fluctuation of  her condition between hyper and hypothyroidism and  stopped all allopathic medicines. Referred by some  of her relatives she consulted us for treatment of her  ailment.
Keywords: Hypothyroidism; thyroid disorder; thyroid stimulating hormone; homoeopathy